Highly planar thieno[3, 2-b]thiophene-diketopyrrolopyrrole-containing polymers for organic field-effect transistors. Issue 42 (11th April 2016) - Liu, Xiaotong; Huang, Jianyao; Xu, Jie; Gao, Dong; Zhang, Weifeng; Shi, Keli; Yu, Gui
Abstract : Two novel thieno[3, 2- b ]thiophene-flanked diketopyrrolopyrrole-based copolymers (PTTDPPTVT and PTTDPPSVS) with high planarity were synthesized and studied as semiconductors in OFETs. Abstract : Two novel thieno[3, 2- b ]thiophene-flanked diketopyrrolopyrrole (TTDPP)-based copolymers PTTDPPTVT and PTTDPPSVS were designed and synthesized in order to investigate their optical, electrochemical, and morphological properties as well as device performance in organic field-effect transistors. By introducing large TTDPP units and highly π-extended moieties di(thiophen-2-yl)ethene or di(selenophen-2-yl)ethene in the conjugated backbone, the copolymers with extremely planar conjugated degree and strongly intermolecular interactions were achieved. The devices based on PTTDPPTVT and PTTDPPSVS showed hole mobilities of 0.437 and 0.067 cm 2 V −1 s −1, respectively. These results demonstrated that the TTDPP unit is a promising electron deficient building block for constructing excellent performance semiconducting materials.